Misperception of alcohol norms: influence of others' comments on perception of norm drinking behaviors - Schnabelrauch, Chelsea A. (Kansas State University, 2013)
Previous research has repeatedly demonstrated that undergraduate students overrate others’ norm comfort with and consumption of alcohol (i.e., Prentice & Miller, 1993). This is a dangerous misperception, as students are increasing their personal alcohol intake and / or frequency in order to match their incorrect perception of how much everyone else is drinking. Already assuming that their peers are more comfortable with, and consume more, alcohol than they do, college students’ perception of norm alcohol use may be influenced by peer comments indicating approval / disapproval of alcohol use. Thus, the present study experimentally tested whether a positive or negative comment in reaction to a portrayal of excessive drinking would influence participants’ perceptions of drinking behavior among their campus peers, and whether the sex of the person making the comment differentially influences participants’ perceptions of each sex’s extent of participation in drinking. Participants’ perceptions of drinking behavior were not influenced by the confederate comment nor confederate sex; however, participants consistently estimated that the drinking norm is higher for males than females. Additionally, female participants perceived the drinking norm to be higher than did male participants. Participants’ ratings of the confederates did differ, however, depending on the comment; participants rated the confederates more favorably when the comment made was negative / criticizing of excessive drinking than when the comment made was positive / endorsing of excessive drinking.
Keywords: Drinking norm; College drinking; Alcohol norm; Drinking perception; Alcohol misperception; Comment influence; Psychology (0621); Social Psychology (0451)